The impact of noise in early childhood settings: A New Zealand perspective - Bates S; Page W; Sue S (New Zealand Council for Educational Research, 2021)
Excessive noise levels in early childhood centres have a direct impact on the learning of young children, as well as on the wellbeing of teachers. Psycho-acoustic studies show that noise is a key factor contributing to elevated adult stress levels and annoyance, leading to lower levels of adult sensitivity to children’s needs and fewer direct interactions with them. Longer term, local and international research indicates correlations between excessive noise in early childhood education (ECE) centres and health problems, such as to hearing loss, voice strain, obesity, diabetes, and cardiac conditions. Noise as a chaos factor in early childhood settings undermines wellbeing of both adults and children. Because noise negatively impacts on quality relationship and communication, children’s language development is also impacted. Yet noise within New Zealand early childhood settings is under-researched, under-regulated, and under-monitored. Drawing on local and international research and on a survey of New Zealand early childhood teachers, this article recommends regulating for the creation of quieter environments for the benefit of teachers and learners, the adults and children in early childhood settings.